2015
DOI: 10.1016/j.yhbeh.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The evolving role of dendritic spines and memory: Interaction(s) with estradiol

Abstract: Memory processing is presumed to depend on synaptic plasticity, which appears to have a role in mediating the acquisition, consolidation, and retention of memory. We have studied the relationship between estrogen, recognition memory, and dendritic spine density in the hippocampus and medial prefrontal cortex, areas critical for memory, across the lifespan in female rodents. The present paper reviews the literature on dendritic spine plasticity in mediating both short and long term memory, as well as the decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 108 publications
2
82
0
2
Order By: Relevance
“…Dysfunction of synaptic connections is recognized as the cause of memory impairments, and significant synapse loss has been observed in mild cognitive impairment (MCI) and in earlier stages of AD (8). In AD mouse models, synapse impairments appear before the onset of memory deficit (9), whereas amelioration of synapse loss by administration of estradiol preserves cognitive functions (10). Earlier investigations into AD-related synaptic damages have been mainly focused on the toxic effects of Aβ (11).…”
mentioning
confidence: 99%
“…Dysfunction of synaptic connections is recognized as the cause of memory impairments, and significant synapse loss has been observed in mild cognitive impairment (MCI) and in earlier stages of AD (8). In AD mouse models, synapse impairments appear before the onset of memory deficit (9), whereas amelioration of synapse loss by administration of estradiol preserves cognitive functions (10). Earlier investigations into AD-related synaptic damages have been mainly focused on the toxic effects of Aβ (11).…”
mentioning
confidence: 99%
“…Nevertheless, it is important that investigators consider the possible effects of sex steroid hormones on neural function and behavior in their experimental designs and data interpretation. However, when thinking about sex differences in brain function or behavior, it is important to note whether differences are due to the activational effects of circulating hormones in adulthood or from organizational effects of hormones in early development, as it has been argued that only the latter can be construed as a true sex difference (McCarthy and Konkle 2005).Numerous recent reviews have discussed the effects of E 2 on learning and memory in females (Korol 2002;Foster 2005;Daniel 2006Daniel , 2013Sherwin and Henry 2008;Barha and Galea 2010;Bimonte-Nelson et al 2010;Gibbs 2010;Kim and Casadesus 2010;Choleris et al 2012;Foster 2012;Frick 2012;Acosta et al 2013;Chisolm and Juraska 2013;Ervin et al 2013;Galea et al 2013;Hogervorst 2013;Luine and Frankfurt 2013;Maki 2013;Bean et al 2014;Luine 2014;Frankfurt and Luine 2015;Tuscher et al 2015). As such, this review will not attempt to provide a comprehensive discussion of all effects of E 2 on learning and memory.…”
mentioning
confidence: 99%
“…In ovariectomized rats, dendritic spine density in ventromedial hypothalamic nucleus (VMN), CA1 region on hippocampus, and medial prefrontal cortex is decreased as compared to gonadal intact rats. 30 The nervous system is capable of plasticity and that the dendritic spine is the major site of this activity. Statistical analysis showed that there was significantly increase the number of neurons after treatment in all groups (p<0.05), but the effect of tomato juice administration, physical exercise (swimming without resistance) and combination of these treatments showed the same effect (p>0.05) There was significant increase of ERβ expression after treatment in all groups (p<0.05) and each of the treatment was have the different effects (p<0.05).…”
mentioning
confidence: 99%